Exact boundary controllability and its applications for a coupled system of quasilinear wave equations with dynamical boundary conditions. (October 2019) - Wang, Yue; Leugering, Günter; Li, Tatsien
Abstract: A constructive method with modular structure is used to obtain the local exact boundary controllability for a coupled system of quasilinear wave equations with local or non-local dynamical boundary conditions. Some applications are given for the chain-like or star-like system of strings coupled via elastic springs, and of strings coupled via Maxwell-type and Kelvin-type viscoelastic springs, respectively.